A failed platform: The Citizen Consensus Conference travels to Chile. (May 2016) - Ureta, Sebastián
This article starts by reviewing the setbacks that the recent Science and Technology Studies literature has identified in the functioning of technologies of democracy, the different arrangements that look to enact deliberation on technoscientific issues. Putting a focus on the Citizen Consensus Conference, it then proposes that several of these setbacks are related to the kind of "work" that these technologies are expected to do, identifying two kinds of it: performing a laboratory-based experiment and constituting a platform for the dissemination of facts. It then applies this framework to study a Citizen Consensus Conference carried out in Chile in 2003. After a detailed genealogy of the planning, implementation and afterlife of this exercise, the article concludes that several of the limitations experienced are derived from a "successful outcome" conceived as solely running a neat lab-based experiment, arguing for the need to incorporate its functioning as a platform with all the associated transformations and messiness.